2021
DOI: 10.24875/ric.21000067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Surgical Care Bundle on the Incidence of Surgical Site Infection in Colorectal Surgery: A Quasi-Experimental Intervention

Abstract: Background: Surgical site infections (SSI) have an important impact on morbidity and mortality. Objective: This study, therefore, sought to assess the effect of a surgical care bundle on the incidence of SSI in colorectal surgery. Methods: We conducted a quasi-experimental intervention study with reference to the introduction of a surgical care bundle in 2011. Our study population, made up of patients who underwent colorectal surgery, was divided into the following two periods: 2007-2011 (pre-intervention) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…It is plausible that immunological disturbances might be able to aggravate the pathogenetic process of SSI by opening the door for microbes, which are harmful for immunocompromised patients. Zarain-Obrador et al evaluated data of 1727 patients, who underwent colorectal surgery given their risk of SSI [ 38 ]. Sixteen percent of patients had emergency surgery.…”
Section: Resultsmentioning
confidence: 99%
“…It is plausible that immunological disturbances might be able to aggravate the pathogenetic process of SSI by opening the door for microbes, which are harmful for immunocompromised patients. Zarain-Obrador et al evaluated data of 1727 patients, who underwent colorectal surgery given their risk of SSI [ 38 ]. Sixteen percent of patients had emergency surgery.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16] Neste trabalho, 20% dos pacientes foram submetidos a cirurgia de urgência, valor próximo ao encontrado em um estudo realizado, que avaliou os fatores de risco para infecção em pacientes e encontrou um percentual de 16,3% de cirurgias consideradas de urgência. 17 Existem fatores que aumentam a chance de um paciente cirúrgico desenvolver uma infecção. Entre eles encontram-se a idade, a condição clínica do paciente, o preparo pré-operatório, o tempo de cirurgia e a classificação quanto ao potencial de contaminação do sítio cirúrgico em relação à presença de microrganismos.…”
Section: Discussionunclassified
“…1 As cirurgias potencialmente contaminadas são realizadas em tecidos colonizados por flora microbiana sem processos de infecção e inflamação, como também em cirurgias com falhas técnicas discretas intraoperatórias. 17 As cirurgias limpas e potencialmente contaminadas apresentam baixo percentual de risco de desenvolvimento de infecção, 7 sendo assim a presença de ISC implica a reflexão quanto à necessidade de identificação dos fatores relacionados a seu desenvolvimento. É necessário levar em consideração todos os aspectos que podem influenciar a maior ocorrência de infecção, como fato de o hospital ser uma instituição de ensino o que contribui para índices maiores de eventos adversos, entre eles as ISCs conforme resultado encontrado em estudo que avaliou esse perfil de hospitais.…”
Section: Discussionunclassified
“…Neutropenia is defned as ANC below 1500 cells per microliter (μL) and is associated with increased susceptibility to infections, diminished infammatory response, and higher mortality [8,9]. Neutropenic patients undergoing abdominal surgery have demonstrated higher rates of postoperative complications, surgical site infections (SSI), and morbidity [10][11][12]. Zarain-Obrador et al [12] reported preoperative neutropenia as an independent predictor of SSI in 1,727 colorectal surgeries.…”
Section: Introductionmentioning
confidence: 99%